Obtaining chitosan sulfate nanoparticles in an aqueous medium and their colloidal protection with polysaccharides - V. S. Erasov; Yu. O. Maltseva (Тонкие химические технологии)
Objectives. To develop a method to obtain a hydrosol of the salt of chitosan with sulfuric acid—chitosanium sulfate (ChS) hydrosol—and to study the effect of various water-soluble polysaccharides on its stability over time, as well as its resistance to indifferent and non-indifferent electrolytes.Methods. κ-Carrageenan, sodium alginate (SA), and xanthan were used as polymers which perform the function of colloidal protection for ChS nanoparticles. Capillary viscometry was used to study the viscosity of polymer solutions, their molecular weight, and their adsorption on ChS. The stability of the sols over time and their resistance to indifferent and non-indifferent electrolytes were evaluated photometrically. The hydrosol particle size was determined by means of dynamic light scattering.Results. On the surface of ChS, κ-carrageenan is adsorbed most strongly over a wide range of concentrations. The graphs of the dependencies of the relative change in the turbidity of sols with the addition of various polysaccharides on their weight concentration at a sol lifetime of 2 days have the shape of curves with a maximum. Sols with the addition of 0.0125% SA and κ-carrageenan in the range of 0.04% have the greatest stability over time. According to dynamic light scattering data, the average particle size of freshly prepared sols with the addition of the polymers to ensure their greatest stability over time are 10.8 nm and 14.6 nm, respectively. For freshly prepared sols without polysaccharides, this size is 24.8 nm. The hydrosol coagulation threshold with an indifferent electrolyte (NaCl) is 9.3 times higher than that with a non-indifferent electrolyte (Na2SO4). κ-Carrageenan and SA protect the hydrosol from coagulation with an indifferent electrolyte (NaCl) at all their used amounts. At the same polymer concentrations, no protection from coagulation with a non-indifferent electrolyte (Na2SO4) was observed.Conclusions. A method was developed to obtain ChS hydrosol with a positive particle charge. The stability of ChS sols over time was studied both without and with the addition of SA, κ-carrageenan, and xanthan. Sol coagulation thresholds with indifferent and non-indifferent electrolytes, as well as the protective numbers for κ-carrageenan and SA against the coagulation of hydrosols with these electrolytes, were established. The mechanism of stability of sols at certain concentrations of water-soluble polysaccharides was explained using data on the adsorption of these polysaccharides on the surface of chitosan treated with a solution of sulfuric acid. Based on the results of the work, it can be concluded that SA and κ-carrageenan can be used for the efficient stabilization of ChS hydrosols over time and for the colloidal protection of ChS from coagulation with sodium chloride.